The Effect of Promotion, Quality of Service and Price on Patient Loyalty with Patient Satisfaction as Mediation - Astarini, Yulfa; Fachrodji, Achmad (IJOSMAS, 2023)
- Research objectives: test and analyze the effect of promotion, quality of service and price on patient loyalty with patient satisfaction as a medium. Type of research: causal associative research with quantitative techniques. Research sample: 160 outpatients at Premier Bintaro Hospital with nonprobability sampling technique used is purposive sampling. Analytical Method: smartPLS SEM software version 4.0. Research results: the effect of promotion on satisfaction with a t-value of 2.33 and estimate 20%, the effect of service quality on satisfaction with a t-value of 2.28 and estimate 57%, the effect of price on satisfaction with a t-value of 2.30 and estimate 46%, the effect of promotion on loyalty with a t-value of 2.06 and estimate 39%, the effect of service quality on loyalty with a t-value of 2.07 and an estimate of 61%, the effect of price on loyalty with a t-value of 4.40 and an estimate of 51%, promotion of loyalty through satisfaction with t-value 2.06 and estimate value 17%, quality of service to loyalty through satisfaction with t-value 2.13 and estimate value 42%, price to loyalty through satisfaction with t-value 2.84 and niali estimate 0.47 or 47%. Conclusion: promotion, quality of service and price have a positive and significant effect on loyalty and satisfaction. Promotion, service quality and price have a positive and significant effect on loyalty through satisfaction, satisfaction has a positive and significant effect on loyalty.